2007
DOI: 10.1016/j.saa.2006.12.080
|View full text |Cite
|
Sign up to set email alerts
|

The Rio Tinto Mars Analogue site: An extremophilic Raman spectroscopic study

Abstract: The Rio Tinto site is recognised as a terrestrial Mars analogue because of the presence of jarosite and related sulfates which have recently been identified by the NASA Mars Exploration Rover "Opportunity" in the El Capitan region of Meridiani Planum on Mars. It has long been known that acidophilic microbial action is responsible for the deep blood-red colour of the water in Rio Tinto, where the pH varies from about 1.5 to 3.0 and the water is rich in iron and sulfur. Following recent Raman spectroscopic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…For detecting them in the frame of future Mars missions, the application of Raman spectroscopy was proposed [38][39][40]. In fact, it was shown that on the Earth carotenoids can unambiguously be detected in lichen encrustations [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…For detecting them in the frame of future Mars missions, the application of Raman spectroscopy was proposed [38][39][40]. In fact, it was shown that on the Earth carotenoids can unambiguously be detected in lichen encrustations [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the characteristics of UV absorption by MAAs, several studies have suggested that these compounds can act as natural screens of UV radiation and should be considered photoprotectants (66,67). The Raman spectrum assigned to a mycosporine-like amino acid compound was reported for a jarosite matrix originating from Rio Tinto, Spain (68) and from hyperarid (Atacama, Chile) shallow subsurface layers (69).…”
Section: Raman Spectrometry Of Microbial Pigments-pure Culture Studiesmentioning
confidence: 99%
“…Raman microspectrometry permits the direct study of pigment type and distribution in endolithic zones in the frame of natural stony samples without sample treatment or extractions. Microbial communities inhabiting rocks from various extreme environments were studied: Antarctic habitats (82-84), volcanic rocks as well as travertines on Svalbard (Norway) (80,85) as well as halophiles from a hot desert (68,86). Raman spectroscopy revealed differences in pigment distribution in chasmolithic and endolithic colonizations of differing lithologies, including those from dolomite, gypsum, or altered orthoquartzite (83,86).…”
Section: Raman Features Of Pigments From Natural Biogeological Samplesmentioning
confidence: 99%
“…48 Finally, in 2007 Edwards et al took a portable system to the Rio Tinto, a river rich in iron and sulfates with an acidic pH. 49 This site is widely considered an analog to the El Capitan region of the Meridiani Planum on Mars. Within the river, key biomarkers, such as carotenoids and scytonemin, and minerals, such as jarosite and gypsum, were detected.…”
Section: Targetsmentioning
confidence: 99%
“…71 Other important minerals include pyroxene, olivine, quartz, jarosite, and gypsum. 49,72,73 Ice is another very important geological sample that could hold key biomarkers and is unique in that water can exist as a solid, liquid, or gas in the atmosphere. Raman has been able to distinguish between different forms of ice with conventional Raman spectrometers 18 and in remote systems (Fig.…”
Section: Targetsmentioning
confidence: 99%